JS1.1 Specific genetic alterations of breast tumors lead to Yo paraneoplastic cerebellar syndromes. (6th September 2019) - Desestret, V; Pissaloux, D; Treilleux, I; Small, M; Robert, M; Rogemond, V; Picard, G; Psimaras, D; Alentorn, A; Honnorat, J
Abstract: BACKGROUND: Paraneoplastic cerebellar degenerations with anti-Yo antibodies (Yo-PCD) are rare syndromes associated with ovarian or breast cancers and caused by an auto-immune response against neuronal antigens expressed by tumor cells. We previously demonstrated in Yo-PCD ovarian cancers an association between massive infiltration of ovarian tumors by activated immune effector cells and recurrent gains and/or mutations of onconeural Yo genes ( CDR2L and CDR2 ), suggesting that such genetic alterations in ovarian tumor cells may trigger immune tolerance breakdown and initiation of the auto-immune reaction against Purkinje cells. MATERIAL AND METHODS: We pursued the characterization of Yo-PCD tumors and specifically studied breast cancer by IHC, FISH, CGH array and RNA sequencing analysis of 17 breast Yo-PCD tumors and by comparing their genetic characteristics with 10 sporadic breast tumors and public databases. RESULTS: We confirmed that specific genetic alterations were also present in breast cancers associated with Yo-PCD. Moreover, this study provides additional evidence for a role of tumor cell specificities in PCD immunopathology by revealing peculiarities in Yo-PCD breast tumors compared to Yo-PCD ovarian cancer. Indeed, not only the CDR2L Yo gene was amplified in 8/9 breast Yo-PCD cancers but also the Erb2/Her2 gene in 15/16 (both genes are on chromosome 17q). In addition to this original Her2 and Yo antigen amplification confirmed by FISH, we observed an overexpression of these proteins by IHC analysis. These Yo-PCD breast cancers are also all negative for hormone receptors (HR). Thus, Yo-PCD breast tumors seem to belong to the molecularly and clinically distinct class of HR-negative and Her2-enriched breast cancers, which represents less than 10 % of breast cancers in the general population. Transcriptomic analysis confirmed that breast Yo-PCD tumors differ by their expression programs from classical breast cancers molecular subtypes. CONCLUSION: Understanding the tumor genetic features leading to the immune breakdown and anti-tumor immune response as well as nervous tissue attack remains challenging and seems to be specific according to the tumor subtypes. Herein, our results suggest that, despite sharing common genetic alterations (copy number variations and mutations affecting Yo genes), the Yo-PCD immunopathogenesis of breast and ovarian cancers differ by involving different tumor-specific molecular pathways.